2017
DOI: 10.1007/s00204-017-1941-x
|View full text |Cite
|
Sign up to set email alerts
|

Study on inter-ethnic human differences in bioactivation and detoxification of estragole using physiologically based kinetic modeling

Abstract: Considering the rapid developments in food safety in the past decade in China, it is of importance to obtain insight into what extent safety and risk assessments of chemicals performed for the Caucasian population apply to the Chinese population. The aim of the present study was to determine physiologically based kinetic (PBK) modeling-based predictions for differences between Chinese and Caucasians in terms of metabolic bioactivation and detoxification of the food-borne genotoxic carcinogen estragole. The PBK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
(76 reference statements)
0
9
0
Order By: Relevance
“…Yang et al (2012) reported significant differences in phenacetin O-deethylation, diclofenac 4′-hydroxylation, (S)-mephenytoin 4′-hydroxylation, and chlorzoxazone 6-hydroxylation reactions, mediated by CYP 1A2, CYP 2C9, CYP 2C19 and CYP 2E1, respectively between Chinese and Caucasian liver microsomal preparations. Previously, we also reported differences between Chinese and Caucasians regarding the metabolic bioactivation and detoxification of the food-borne genotoxic carcinogen estragole, resulting in a predicted 4.5fold lower formation of the ultimate carcinogenic metabolite of estragole with similar rates of detoxification in Chinese as compared to the Caucasians, and thus a possible lower risk of estragole exposure for the average Chinese at similar levels of exposure (Ning et al 2017).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Yang et al (2012) reported significant differences in phenacetin O-deethylation, diclofenac 4′-hydroxylation, (S)-mephenytoin 4′-hydroxylation, and chlorzoxazone 6-hydroxylation reactions, mediated by CYP 1A2, CYP 2C9, CYP 2C19 and CYP 2E1, respectively between Chinese and Caucasian liver microsomal preparations. Previously, we also reported differences between Chinese and Caucasians regarding the metabolic bioactivation and detoxification of the food-borne genotoxic carcinogen estragole, resulting in a predicted 4.5fold lower formation of the ultimate carcinogenic metabolite of estragole with similar rates of detoxification in Chinese as compared to the Caucasians, and thus a possible lower risk of estragole exposure for the average Chinese at similar levels of exposure (Ning et al 2017).…”
Section: Introductionmentioning
confidence: 79%
“…Based on these results for the rat model, the developed PBK model for lasiocarpine or riddelliine are considered an adequate first approximation to describe the in vivo situation for human. An additional approach to describe the performance of the human PBK model for lasiocarpine and riddelliine for the human populations, especially for the difference between the Chinese and the Caucasian populations, was done based on the approach described previously (Ning et al 2017). In this approach a comparison is made between the predicted inter-ethnic differences for the dose-dependent concentration of lasiocarpine and riddelliine in the liver blood and the observed inter-ethnic differences in hepatic metabolising enzymes that mainly catalyse the depletion of lasiocarpine or riddelliine.…”
Section: Pbk Model Prediction and Evaluationmentioning
confidence: 99%
“…It is worth to note that microsomal incubations are well accepted and also validated to define kinetic parameters for metabolism and clearance in PBK modeling (Al-Subeihi et al., 2012; Lu et al , 2009; Mosquin et al , 2009; Ning et al , 2017; Punt et al , 2008, 2009; Timchalk et al , 2002). Furthermore experimental data shown that kinetic data derived from microsomal incubations and hepatocyte incubations are comparable as Di et al (2012) reported that the intrinsic clearance for compounds predominantly mediated by CYP450 obtained from microsomal incubations are comparable with that obtained from hepatocyte incubations.…”
Section: Methodsmentioning
confidence: 99%
“…However, when developing these PBK models, interethnic differences have not yet been taken into account. Biomonitoring studies have reported OP metabolite levels in maternal urine in China to be higher than those in maternal urine in developed countries (Wang et al , 2012), and interethnic differences in bioactivation and detoxification have already been reported for other compounds than OPs (Ning et al , 2017; Zhang et al , 1990). Hence, it is of importance to include the interethnic differences in kinetics when developing PBK models for CPF in human.…”
mentioning
confidence: 99%
“…Over the last decade, several proof-of-principle studies indicated that combining in vitro toxicity assays with physiologically based kinetic (PBK) modeling, which describes the absorption, distribution, metabolism and excretion (ADME) of a compound in a defined species, can adequately predict in vivo dose–response curves (Louisse et al 2017 ; Rietjens et al 2011 ). For example, quantitative in vitro to in vivo extrapolation (QIVIVE) using PBK modeling-based reverse dosimetry was shown to adequately predict the in vivo toxicity for different endpoints, including developmental toxicity (Li et al 2017 ; Louisse et al 2010 ; Strikwold et al 2013 , 2017 ), liver toxicity (Ning et al 2017 ), nephrotoxicity (Abdullah et al 2016 ) and neurotoxicity (Zhao et al 2019 ). To further explore the potential applicability of this in vitro–in silico approach, the aim of the present study was to investigate whether the PBK modeling-based reverse dosimetry can be extended to predict in vivo cardiotoxicity in human, thereby providing a novel testing strategy for cardiac safety testing.…”
Section: Introductionmentioning
confidence: 99%